METAXYTHERIUM MEDIUM (MAMMALIA: SIRENIA) FROM UPPER MIOCENE SEDIMENTS OF THE ARENARIA DI PONSANO FORMATION (TUSCANY, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
Records of Metaxytherium medium (Mammalia: Sirenia) from Tononian (Late Miocene) sediments from che Arenaria di Ponsano Formation (Tuscany, Italy) are described. They consist of fragmentary specimens, including several partial cranial elements representing at least three skulls, two humeri, fragments of venebrae and some incomplete ribs. The new Tuscan records confirm che wide diffusion of Metaxytherium in the Mediterranean during the Miocene. This sirenian's occurrence in the Arenaria di Ponsano sediments is in accordance with the shelf environment indicated by other fossils. The low sea bottom was at least partially covered by segrass meadows, the food source of this dugongid.